Precision of 3.0 Tesla quantitative magnetic resonance imaging of cartilage morphology in a multicentre clinical trial. Issue 12 (18th February 2008) - Eckstein, F; Buck, R J; Burstein, D; Charles, H C; Crim, J; Hudelmaier, M; Hunter, D J; Hutchins, G; Jackson, C; Kraus, V Byers; Lane, N E; Link, T M; et al.
Abstract : Objective: Quantitative MRI (qMRI) of cartilage morphology is a promising tool for disease-modifying osteoarthritis drug (DMOAD) development. Recent studies at single sites have indicated that measurements at 3.0 Tesla (T) are more reproducible (precise) than those at 1.5 T. Precision errors and stability in multicentre studies with imaging equipment from various vendors have, however, not yet been evaluated. Methods: A total of 158 female participants (97 Kellgren and Lawrence grade (KLG) 0, 31 KLG 2 and 30 KLG 3) were imaged at 7 clinical centres using Siemens Magnetom Trio and GE Signa Excite magnets. Double oblique coronal acquisitions were obtained at baseline and at 3 months, using water excitation spoiled gradient echo sequences (1.0×0.31×0.31 mm 3 resolution). Segmentation of femorotibial cartilage morphology was performed using proprietary software (Chondrometrics GmbH, Ainring, Germany). Results: The precision error (root mean square coefficient of variation (RMS CV)%) for cartilage thickness/volume measurements ranged from 2.1%/2.4% (medial tibia) to 2.9%/3.3% (lateral weight-bearing femoral condyle) across all participants. No significant differences in precision errors were observed between KLGs, imaging sites, or scanner manufacturers/types. Mean differences between baseline and 3 months ranged from <0.1% (non-significant) in the medial to 0.94% (p<0.01) in the lateral femorotibial compartment, and were 0.33% (p<0.02) for the total femorotibial subchondral bone area. Conclusions: qMRI performed at 3.0 T provides highly reproducible measurements of cartilage morphology in multicentre clinical trials with equipment from different vendors. The technology thus appears sufficiently robust to be recommended for large-scale multicentre trials.